PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PENGURUSAN (SKCK) SURAT KETERANGAN CATATAN KEPOLISIAN DI SATUAN INTELKAM POLRES SITUBONDO - Hadi Wijono; Anton Hari Wibowo (ACTON, 2017)
The purpose of this study is to determine the Influence of Service Quality Against Public Satisfaction in the Management of Police Note Certificate (SKCK) In Unit Intelkam Polres Situbondo. The research approach is quantitative research. The population is the community receiving service from the last 3 months as many as 1200 people. The sample in this research is 92 people. Data collection techniques are questionnaires, interviews, observation, documentation and literature study. Data were analyzed by multiple regression. The result of analysis stated that there is Influence of Service Quality to Satisfaction of Society in Handling (SKCK) of Police Note Certificate at Intelligence Unit of Situbondo Resort Police.